Examining Package Tourists’ Experience on Overall Package Tour Satisfaction and Behavioral Intentions: First-Time Versus Repeat Package Tourists - Atsız, Ozan (2021)
This paper examines the influence of package tour experience dimensions (i.e., educational, entertainment, escapism, and esthetic experience) on tour satisfaction and behavioral intentions by comparing first-time and repeat package tourists. For this purpose, a self-administered questionnaire was distributed to tourists visiting Istanbul with a package tour. A convenience sampling was adopted and a total of 375 usable questionnaires was included in the analysis. Partial Least Squares Structural Equation Modeling approach was used to examine the data. The study findings indicated that education and esthetic experience affects overall package tour satisfaction for first-time tourists; entertainment and esthetic experience affects overall package tour satisfaction for repeat tourists. Furthermore, the overall package tour satisfaction mediates between these variables and behavioral intentions for both groups. The findings have suggested theoretical and managerial implications, limitations, and suggestions for further studies.